Kemampuan numerasi siswa kelas IV dalam materi pecahan di SD 008 Palembang - Claudio Angga Ramadona; Nyiayu Fahriza Fuadiah; Nora Surmilasari (IKIP Siliwangi, 2026)
Numeracy skills are fundamental skills that include understanding concepts, calculation skills, and the application of mathematics in daily life. This research aims to describe the numeracy skills of fourth-grade students in fraction material at SD 008 Palembang. This study uses a quantitative descriptive approach with instruments in the form of written tests consisting of multiple-choice questions and essays. The subjects of the research consisted of 27 fourth-grade students. The results of the study indicate that the numeracy skills of the students in fraction material are categorized as moderate, both overall. or indicators. Students are able to solve simple fraction problems, such as finding a common denominator and determining equivalent fractions, but still experience difficulties in solving problems that involve complex fraction operations and their application in word problems. This difficulty indicates the need for strengthening conceptual understanding through a more contextual and varied learning approach. This study recommends that teachers use more interactive methods and increase contextual practice problems in order to improve students' numeracy skills.